Spectrum of Hepatic Involvement in Children with Dengue Infection (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Nowadays, dengue infection, a viral disease spread by arthropods is the most prevalent and significant for humans. Though not hepatotropic, the dengue virus often causes liver damage. Liver dysfunction in dengue cases may result from direct viral impact on liver cells or uncontrolled immune response by the host.Objective: To estimate the range of hepatic involvement in dengue infection in children.Methods: This prospective observational study was conducted at the Paediatric Indoor Department of Combined Military Hospital, Dhaka, Bangladesh from April 2023 to July 2024. A total of 70 dengue NS1 or dengue antibody IgM-positive children aged 2-12 years were enrolled as the study subjects using a purposive sampling technique. For data analysis, SPSS v26 was applied.Results: Among the participants while analyzing the hepatic involvement it was observed that 56% had hepatomegaly, 49% had ascites and 26% had serum bilirubin levels above 1 mg/dl. Elevated aspartate aminotransferase (AST) levels were found in 91%, elevated alanine aminotransferase (ALT) levels in 81%, elevated alkaline phosphatase (ALP) levels in 70% and 36% had a prolonged international normalized ratio (INR) greater than 1.5. Conclusion: In children with dengue infection, the most common hepatic involvements are elevated aspartate aminotransferase (AST), alanine aminotransferase (ALT) alkaline phosphatase (ALP) levels and hepatomegaly. Additionally, ascites, hyperbilirubinemia and prolonged INR may also be observed.JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 30-32